Analysis Of The Effectiveness Of Government Accounting System Digitalization On Financial Reporting Quality In Regional Governments Of East Kalimantan - Syafa Ananda Descianti; Rifandi Fauji Pratama; Rimi Gusliana Mais (International Journal of Economics and Development, 2026)
This study aims to analyze the effectiveness of government accounting system digitalization regional government financial reports in five regional governments in East Kalimantan, namely Balikpapan City, Samarinda City, Kutai Kartanegara Regency, North Penajam Paser Regency, and Berau Regency. This research addresses the inconsistency of previous findings and the limited studies that comprehensively examine the effectiveness of government accounting system digitalization on regional financial reporting quality across different local government contexts, particularly in East Kalimantan. This study employs a qualitative descriptive approach. Secondary data were obtained from Regional Government Financial Reports (LKPD), BPK audit reports, and official regional government portals. The data were analyzed using descriptive and comparative analysis techniques. The results show that the implementation of the Regional Government Information System (SIPD) has generally been effective in improving financial management, particularly in terms of system integration, data accuracy, reporting timeliness, and transparency. The achievement of Unqualified Opinions (WTP) by all research objects indicates relatively good financial reporting quality. However, differences in human resource capacity, technological infrastructure, and system integration readiness still affect the effectiveness of digitalization across regions. The study contributes to the development of public sector accounting digitalization studies and provides practical recommendations for regional governments to improve digital infrastructure, employee competence, and system optimization to support transparent and accountable financial reporting.